Cytohistologic Correlation Study of Thyroid Lesions with Emphasis on the Diagnostic Pitfalls - Ghadeer A. Mokhtar; Rana Y. Bokhary (Journal of King Abdulaziz University: Medical Sciences, 2023)
Fine needle aspiration of thyroid is proven to be the most economical and reliable diagnostic tool for distinguishing neoplastic from non-neoplastic nodules for better selection of patients for surgery. The aim of this study is to evaluate the diagnostic accuracy of thyroid cytology performed at our institution by correlating its results with final histopathological diagnosis. This retrospective study used two-hundred and seventy-one cases of thyroid cytology performed at King Abdulaziz University Hospital between 1995 and 2007. The corresponding histopathological slides were reviewed. The sensitivity and specificity of cytology for detecting neoplasia at our institute were calculated at 71% and 93%, respectively. The most common benign lesion diagnosed was multinodular goiter (46%), and the most common malignancy was Papillary Thyroid Carcinoma (16%). The major cause of false positive diagnosis is the overlapping cytological features in hyperplasia that can be misinterpreted as features of neoplasia; whereas the main reason of false negative diagnosis is failure to recognize the follicular variant of papillary thyroid carcinoma. The study confirmed the efficiency of cytology in the evaluation of both nodular and diffuse thyroid lesions. However; cytopathologists should be aware of the potential diagnostic pitfalls in order to achieve a higher rate of diagnostic accuracy.